Heat and moisture transport characteristics in permafrost embankment under seasonal rainfall - Wang, Zhanxu; Wang, Laifa; Wang, Xinyan; Ming, Feng (Frontiers in Earth Science, 2024)
The Tibetan Plateau has exhibited a discernible trend towards increased precipitation over the past 50 years. However, previous research predominantly focused on thermal stability of permafrost without the consideration of water flux boundary conditions, and therefore ignored the dynamics of water migration and its impacts on the embankment stability. To bridge this gap, a novel water-heat transfer model incorporating rainfall and water migration was developed and subsequently validated using monitored data. Comparative analyses were then conducted across three distinct rainfall intensities to investigate the variations in the moisture and temperature of superficial soil. Results indicate rainfall events exert a notable cooling effect during warm seasons but have little influence on cooling during cold seasons. By increasing the latent heat of evaporation, sensible heat and reducing the soil heat flux, rainfall results in embankment cooling, and the cooling effect correlates positively with rainfall intensity. Disregarding the water flux boundary conditions will overestimate the embankment temperature and underestimate the variation of water content, especially at the superficial soil. Rainfall results in a decline in water vapor flux and an increase in liquid water flux, which facilitates rapid downward transport and accumulation of liquid water. Despite the increased convective heat transfer of liquid water, the decrease in heat conduction, latent heat of evaporation and convective heat transfer of water vapor in the embankment is more pronounced. Rainfall changes the stability of permafrost embankment mainly by adjusting the energy distribution, which delays temperature increases in the underlying permafrost. When predicting the stability of permafrost, it is recommended to incorporate the water flux boundary conditions.